EFEKTIVITAS METODE PROBLEM SOLVING TERHADAP HASIL BELAJAR PPKn KELAS XI MAS AL-MUSTAQIM KUBU RAYA - Baniah, Baniah; Sulistyarini, Sulistyarini; Utomo, Bambang Budi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to find out how the problem solving learning method towards student learning outcomes in PPKn learning in class XI MAS Al-Mustaqim Sungai Raya Kabupaten Kubu Raya. The research method used is an experimental method with a pre-experimental design research form, namely by using a one-group pretest-posttest design with IPS XI class students Al-Mustaqim Sungai Raya. Samples used with purposive techniques. Class XI IPS 2 is a class that is used as an experimental class. The learning process in the experimental class uses problem solving learning methods. The data engineering tool used is the thesis test data. The analysis required includes validity test, difficulty level, different power index, reality test, normality test, homogeneity test and hypothesis test with a significance level of 5%. In the calculation process using the SPSS version 16.0 assistance program. The results showed that there were several methods used in KDP learning in class XI MAS Al-Mustaqim Sungai Raya Kabupaten Kubu Raya, and from the results of data analysis using t test that was searched for sig values. (2-tailed) of 0.000 <0.05, and by using the effect size measurement, the result is 2.12. Den Ho Ho.Â Keywords: method of learning problem solving, student learning outcomes, PPKn